2015
DOI: 10.1155/2015/819084
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow-Derived Mesenchymal Stromal Cells Differentially Inhibit Cytokine Production by Peripheral Blood Monocytes Subpopulations and Myeloid Dendritic Cells

Abstract: The immunosuppressive properties of mesenchymal stromal/stem cells (MSC) rendered them an attractive therapeutic approach for immune disorders and an increasing body of evidence demonstrated their clinical value. However, the influence of MSC on the function of specific immune cell populations, namely, monocyte subpopulations, is not well elucidated. Here, we investigated the influence of human bone marrow MSC on the cytokine and chemokine expression by peripheral blood classical, intermediate and nonclassical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 91 publications
1
29
0
Order By: Relevance
“…ICOSL expression in MSCs has been reported by us and other groups163233. Here, we provide evidence that ICOSL expression in MSCs promotes CD4 + CD25 + FoxP3 + Treg induction.…”
Section: Discussionsupporting
confidence: 79%
“…ICOSL expression in MSCs has been reported by us and other groups163233. Here, we provide evidence that ICOSL expression in MSCs promotes CD4 + CD25 + FoxP3 + Treg induction.…”
Section: Discussionsupporting
confidence: 79%
“…BM-MSCs exhibit significant immunomodulatory effects in vivo , modulating T-cell proliferation rates, activating a T-regulatory cell phenotype (CD8 + CD28 − Treg), and producing a general suppressive effect on CD4+ and CD8+ T cells (Castro-Manrreza and Montesinos, 2015, Liu et al, 2015). BM-MSC transplantation reduces levels of pro-inflammatory cytokines, including interleukin(IL)-1β and IL-6, upregulates the expression of anti-inflammatory cytokines, such as IL-4, IL-10, and transforming growth factor-β1, and lessens the number of activated microglia in ischemic tissue (Chen et al, 2013; McGuckin et al, 2013; Castro-Manrreza and Montesinos, 2015; Laranjeira et al, 2015). …”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%
“…In previous studies, we demonstrated that BM‐MSCs possess the ability to inhibit the proinflammatory response by freshly isolated myeloid dendritic cells, monocytes, and CD4 + and CD8 + T cells, regardless of the functional compartment they were included in, in healthy individuals (Laranjeira et al, ; Laranjeira et al, ). Here, we investigate whether this inhibitory effect is maintained in RA patients' immune cells.…”
Section: Introductionmentioning
confidence: 96%